Overexpression of Aquaporin 1 in the Tunica Vaginalis May Contribute to Adult-Onset Primary Hydrocele Testis - Mami Hattori; Akiko Tonooka; Masayoshi Zaitsu; Koji Mikami; Ayako Suzue-Yanagisawa; Toshimasa Uekusa; Takumi Takeuchi (Advances in Urology)
To investigate the cause of the adult-onset primary noncommunicating hydrocele testis, protein expressions of water channel aquaporins (AQPs) 1 and 3 in the tunica vaginalis were assessed. Frozen tunica vaginalis specimens from patients with adult-onset primary hydrocele testis and control male nonhydrocele patients were subjected to Western blot analysis for the detection of AQP1 and AQP3 proteins. Paraffin-embedded sections of tunica vaginalis specimens were histochemically stained with anti-AQP1 and anti-AQP3 antibodies as well as an anti-podoplanin antibody to stain lymphatic endothelia. Hydrocele fluid was subjected to biochemical analysis. AQP1 protein expression in the tunica vaginalis was significantly higher in patients with adult-onset hydrocele testis than in the controls. The AQP3 protein was not detected in the tunica vaginalis. Histochemically, AQP1 expression in the tunica vaginalis was localized in vascular endothelial and smooth muscle cells. The densities of AQP1-expressing capillaries and lymphatic vessels were similar between the tunica vaginalis of the controls and those of hydrocele patients. Sodium levels were higher in the hydrocele fluid than in the serum. In conclusion, overexpression of the AQP1 protein in individual capillary endothelial cells of the tunica vaginalis may contribute to the development of adult-onset primary noncommunicating hydrocele testis as another aquaporin-related disease.